How Teichoic Acids Could Support a Periplasm in Gram-Positive Bacteria, and Let Cell Division Cheat Turgor Pressure - Erickson, Harold P. (Frontiers in Microbiology, 2021)
The cytoplasm of bacteria is maintained at a higher osmolality than the growth medium, which generates a turgor pressure. The cell membrane (CM) cannot support a large turgor, so there are two possibilities for transferring the pressure to the peptidoglycan cell wall (PGW): (1) the CM could be pressed directly against the PGW, or (2) the CM could be separated from the PGW by a periplasmic space that is isoosmotic with the cytoplasm. There is strong evidence for gram-negative bacteria that a periplasm exists and is isoosmotic with the cytoplasm. No comparable studies have been done for gram-positive bacteria. Here I suggest that a periplasmic space is probably essential in order for the periplasmic proteins to function, including especially the PBPs that remodel the peptidoglycan wall. I then present a semi-quantitative analysis of how teichoic acids could support a periplasm that is isoosmotic with the cytoplasm. The fixed anionic charge density of teichoic acids in the periplasm is ~0.5 M, which would bring in ~0.5 M Na+ neutralizing ions. This approximately balances the excess osmolality of the cytoplasm that would produce a turgor pressure of 19 atm. The 0.5 M fixed charge density is similar to that of proteoglycans in articular cartilage, suggesting a comparability ability to support pressure. An isoosmotic periplasm would be especially important for cell division, since it would allow CM constriction and PGW synthesis to avoid turgor pressure.